HAK DAN KEWAJIBAN ANAK DALAM UNDANG-UNDANG NO 35 TAHUN 2014 TENTANG PERUBAHAN UNDANG-UNDANG NO 23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK - Apri Rotin Djusfi (Prodi Ilmu Hukum, Universitas Teuku Umar, 2018)
The existence of the Child Protection Act is a clear proof that the child should be protected. But we also should not see from one aspect, sometimes the existence of the Child Protection Act could be a dilemma. Where educators are faced with a problem related to the process of education and fostering of children. In addition there are things that must be considered about the obligations of children. This legal research is conducted to find solutions to legal issues that arise in the community how the legal protection for teachers related to punishment cases associated with the Child Protection Act. This research used normative law research method, the type of research used is normative juridical, the approach taken is the statutory approach (statute approach) In carrying out its duties as set in Law Number 14 Year 2005 About Teachers and lecturers, Regulation Government Number 74 Year 2008, then the teacher is given academic freedom to perform the methods that exist.In addition Teachers can also give awards and also give sanctions to students Teachers have the freedom to impose sanctions to students who violate the norms of religion, norms of decency, norm modesty, written or unwritten rules set by the teacher, education unit level regulations, and legislation in the learning process under its authority, such sanctions may be warning and / or warning, both oral and written, and educational punishment according to the method of education dikan, teacher code of ethics, and legislation.Keywords: Children, Teacher, Legal Protection